2000
DOI: 10.1088/0953-8984/12/26/307
|View full text |Cite
|
Sign up to set email alerts
|

The time-dependent process of oxidation of the surface of Bi2Te3studied by x-ray photoelectron spectroscopy

Abstract: The process of oxidation of the Bi2Te3 surface was investigated by x-ray photoelectron spectroscopy (XPS). The oxidized surface layer was found to have a definite thickness, with configurations where O is bonded with Bi and Te, and Bi and Te are bonded with three and four oxygens, respectively. The oxidation time dependence of the oxidized layer thickness d(t) estimated from the XPS behaved as (t-t0)1/2 when d(t) was smaller than the thickness of a single oxidized quintuple atomic layer in our oxide model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
120
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 16 publications
32
120
2
Order By: Relevance
“…The UHV conditions of this system ensure that films are free from ex situ contamination. [18,23,24].…”
Section: Film Growth and Characterizationmentioning
confidence: 99%
“…The UHV conditions of this system ensure that films are free from ex situ contamination. [18,23,24].…”
Section: Film Growth and Characterizationmentioning
confidence: 99%
“…Most of these materials have zT close to unity, but they are not stable in air due to the oxidation at these temperatures. 10 Oxide materials are inexpensive, abundant in nature, non-toxic, and environmentally friendly. These materials possess high chemical and thermal stability which makes them suitable for high temperature thermoelectric application in air.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the surface electronic properties of the three-dimensional topological insulators (TIs) were affected by the surface adsorption of residual gases, 2 air, 3 CO, 4 H 2 O, 5 and oxygen. 7,8 In particular, the air exposure over several hours apparently causes the surface oxidation and environmental doping. [6][7][8] It was demonstrated that oxidation of Bi 2 Se 3 results in a complex band structure because of hybridization of the O-derived states with the substrate states.…”
mentioning
confidence: 99%
“…7,8 In particular, the air exposure over several hours apparently causes the surface oxidation and environmental doping. [6][7][8] It was demonstrated that oxidation of Bi 2 Se 3 results in a complex band structure because of hybridization of the O-derived states with the substrate states. 9 The formation of intrinsic oxides observed on the (0001) Bi 2 Se 3 and Bi 2 Te 3 surfaces can be responsible for the change of sign in surface conductivity with time 10 and even for deterioration of the topological surface states properties 7 as well as for reduction of the spin current.…”
mentioning
confidence: 99%